2009
DOI: 10.4161/auto.5.2.7328
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of unusual families of ATG8-like proteins and ATG12 in the protozoan parasiteLeishmania major

Abstract: Leishmania major possesses, apparently uniquely, four families of ATG8-like genes, designated ATG8, ATG8A, ATG8B and ATG8C, and 25 genes in total. L. major ATG8 and examples from the ATG8A, ATG8B and ATG8C families are able to complement a Saccharomyces cerevisiae ATG8-deficient strain, indicating functional conservation. Whereas ATG8 has been shown to form putative autophagosomes during differentiation and starvation of L. major, ATG8A primarily form puncta in response to starvation-suggesting a role for ATG8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(149 citation statements)
references
References 77 publications
8
136
0
Order By: Relevance
“…For example, it has been initially suggested that the second Atg12-based conjugation system was absent in trypanosomatids. 18 However, later reports 14,15,23 identify Atg5 and Atg10 orthologues, recently experimentally characterized. 23 Interestingly, despite the identification…”
Section: Genomic Predictions Regarding Autophagy and Its Evolution Inmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, it has been initially suggested that the second Atg12-based conjugation system was absent in trypanosomatids. 18 However, later reports 14,15,23 identify Atg5 and Atg10 orthologues, recently experimentally characterized. 23 Interestingly, despite the identification…”
Section: Genomic Predictions Regarding Autophagy and Its Evolution Inmentioning
confidence: 99%
“…Using bioinformatics to map the distribution of known autophagy-related proteins in extant eukaryotes, however, indicates that among the protists canonical autophagy has been subjected to elaboration, moderation and even loss on multiple occasions (Fig. 2). 14 As exemplified by the experimental characterization of autophagy in malarial parasites (discussed under the heading 'Autophagy in Apicomplexa'), or the molecular characterization of ATG8 paralogues in Leishmania major 23 the cellular consequences of likely moderation to canonical autophagy, or the paralogue expansion of core ATGs are already under investigation in some species. The availability of reverse genetic tools for many of the other protists in which core ATGs have either been lost or subject to paralogue expansion, means that other variations in autophagy that are apparent at the genomic level should be amenable to experimental investigation, too.…”
Section: Genomic Predictions Regarding Autophagy and Its Evolution Inmentioning
confidence: 99%
See 2 more Smart Citations
“…17,34 We examined whether PbATG8 could likewise functionally complement an atg8Δ yeast strain. To assay complementation of autophagy, PbATG8 was expressed under the control of the PGK (phosphoglycerate kinase) promoter and processing of the precursor form of aminopeptidase I (prApe1) was monitored by western blotting.…”
Section: Plasmodium Atg8 Does Not Interact With the Mammalian Or Yeasmentioning
confidence: 99%